(untitled) (Международный научный журнал «Инженер», 2026)
This article investigates the correlation between the potential for sand encroachment on a newly constructed railway line and the annual precipitation levels. An expert survey was conducted among specialists directly and indirectly involved with this issue, alongside a statistical analysis of natural and climatic winter-spring precipitation over several years in regions where the under-construction railway intersects dune sands. The annual precipitation data were compared with the occurrence of sand drifts. The results of the expert survey, monitoring of potential railway sand encroachment, and precipitation analysis are presented. It was established that the manifestation of sandstorms, and consequently the potential for sand encroachment on infrastructure, is dependent on the amount of rainfall during the winter-spring period. Utilizing the findings of this research will enable the elimination of unnecessary annual measures for protecting the new railway line from sand drifts, specifically those related to the stabilization of mobile sands.